2005
DOI: 10.1111/j.1439-0523.2004.01059.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative efficiency of different Gramineae genera for haploid induction in triticale and triticale x wheat hybrids through the chromosome elimination technique

Abstract: The study was undertaken to evaluate the relative efficiency of different Gramineae genera for haploid induction in triticale (xTriticosecale) and triticale x wheat (Triticum aestivum) hybrids through the chromosome elimination (wheat x maize, Zea mays) system. Eight intergenotypic triticale and 15 triticale x wheat crosses were subjected to hybridization with nine different Gramineae genera viz., Z. mays, Sorghum bicolor, Pennisetum americanum, Setaria italica, Festuca arundinacea, Imperata cylindrica, Cynodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 14 publications
(12 reference statements)
3
20
0
2
Order By: Relevance
“…However, the unsynchronized flowering of these 2 species complicates the hybridization process. Chromosome elimination via Triticum aestivum L. × Imperata cylindrica L. interspecific hybridization, which was first reported by and Pratap et al (2005), is a relatively new and promising technique. Imperata cylindrica L. is actually a perennial invasive weed that synchronously blooms with wheat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the unsynchronized flowering of these 2 species complicates the hybridization process. Chromosome elimination via Triticum aestivum L. × Imperata cylindrica L. interspecific hybridization, which was first reported by and Pratap et al (2005), is a relatively new and promising technique. Imperata cylindrica L. is actually a perennial invasive weed that synchronously blooms with wheat.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, obtaining higher percentages of haploid regenerants from all the studied species proved that this technique, unlike the others, is not genotypespecific . Imperata cylindrica L. mediated chromosome elimination has been applied to date only on the species Triticum aestivum L. Pratap et al, 2005;Komeda et al, 2007;Tayeng et al, 2012) and Triticum aestivum L. × Secale cereale L. hybrids (Kishore et al, 2011). Therefore, the objective of the present study was to evaluate the possibility of obtaining dihaploid durum wheat (Triticum durum L.) plants by interspecific hybridization with Imperata cylindrica L.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that wheat haploids are formed by crossing with I. cylindrica, a wild grass remotely related to wheat Pratap et al, 2005). This novel haploid induction method has two great advantages in practical application, (1) high frequency of haploid induction irrespective of wheat genotypes, and (2) natural coincidence of flowering period of wheat and I. cylindrica under subtemperate condition.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the coincidence of flowering period between wheat and I. cylindrica enables us to obtain fresh pollen of I. cylindrica freely. From these points, I. cylindrica is expected to be employed in wheat haploid production alternative to maize Pratap et al, 2005) Wheat haploid induction using I. cylindrica pollen has been reported only in India so far Pratap et al, 2005). I. cylindrica is merely a wild grass and therefore has uneven genotypes (Matumura et al, 1983;Matumura and Nakajima, 1988;Cheng and Chou, 1997), which does not ensure that I. cylindrica distributed in other regions can induce wheat haploid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation